Utilization of Electronic Medical Records and Service Delivery at Medicus Health Care Kabale Municipality. - Kukunda, Tash (Kabale University, 2023)
The study conducted was about the utilization of electronic medical records and service delivery at Kabale, Municipality. The objectives of the study were to find out the types of electronic medical records found at Medicus Healthcare Kabale Municipality, to establish the impacts of utilization of electronic medical records and service delivery at Medicus Healthcare Kabale Municipality, to assess the challenges facing utilization of electronic medical records and service delivery at Medicus healthcare Kabale Municipality, to establish the possible solutions to the challenges facing utilization of electronic medical records and service delivery Medicus healthcare Kabale Municipality. The study used a descriptive research design. The data collection methods used included the interview, observation, and content data analysis which was checked for their validity and reliability by the university supervisor before going to the field. Data collected was analyzed using thematic analysis and content analysis and a purposive sampling technique was used to get the sample. The findings revealed the types of electronic medical records kept at MHC for example; the Physician Order Entry, Administrative records, Laboratory records Out-patient and inpatient electronic records, and Pharmacy records. The impact of the utilization of electronic medical records on service delivery was; quick in retrieving information of the patients coming for a review, improved on-job performance of the health workers, record keeping and reliable storage making it easy to access the records, capture patient information enabled them to accomplish their tasks more quickly. The study found out the challenges faced while utilizing electronic medical records and service delivery like; as inadequate electricity power supply and power outages causing delays in the health workers' performance of their tasks, poor internet connectivity causing failure to access the system, high costs in maintain the system for they have to pay for it monthly and power shedding. All these challenges hindered the effectual performance of the health workers at MHC. However, possible solutions were identified which included getting a standby power source, Training the staff, proper planning, and taking safe EMR precautions.